Cullin3 aggravates the inflammatory response of periodontal ligament stem cells via regulation of SHH signaling and Nrf2. Issue 1 (1st January 2021) - Chen, Wanhong; Su, Jiangling; Cai, Shixiong; Shi, Chun
ABSTRACT: It is found that the activation of Sonic Hedgehog (SHH) signaling pathway is related to the degree of inflammation in patients suffering from periodontitis. Cullin3 (CUL3), an important ubiquitin ligase, can control SHH signaling. In this study, we were dedicated to clarify the roles of SHH and CUL3 in P. gingivalis -LPS (Pg-LPS)-treated periodontal ligament stem cells (PDLSCs). In this study, cell viability was detected using cell counting kit-8 (CCK-8). The inflammatory cytokines of PDLSCs were estimated by enzyme-linked immunosorbent assay (ELISA). With the application of western blots, the protein levels of SHH, Gli1 and NF-E2-related factor 2 (Nrf2) were determined. Alkaline phosphatase staining and Alizarin red staining were performed to evaluate the differentiation and mineralization capabilities of PDLSCs. The apoptotic cells were screened using TUNEL staining. The results showed that Pg-LPS inhibited cell viability and triggered inflammation of PDLSCs. Overexpression of CUL3 weakened the differentiation and mineralization capabilities of PDLSCs. Moreover, CUL3 overexpression aggravated inflammation and cell apoptosis induced by Pg-LPS. It is worth noting that although the protein levels of SHH, Gli1 and Nrf2 were elevated in PDLSCs treated with Pg-LPS, overexpression of CUL3 decreased the expressions of Gli1 and Nrf2. Overall, SHH/Gli1 and Nrf2 were involved in the inflammation and cell apoptosis of PDLSCs, which was dominated by CUL3. Graphical abstract: uf0001